Personal identity in the space of virtual culture: on the example of geek and glam subcultures - Osadcha, L. V. (Anthropological Measurements of Philosophical Research, 2022)
Purpose. The article presents exploring the cultural and anthropological traits of consumers and producers of cultural services and products in the digital epoch. There have been singled out two types of cultural subjectivity according to the aim of a person’s activity in the virtual net: either production of things, services, and technologies or the consumption and creative use of all mentioned innovations. So these sociocultural formations are called "geek" and "chic" subcultures. Theoretical basis. The historical genealogy of the definitions was analyzed, so as the changes in social esteem of the contribution of geeky persons to modern art and design practices. Social and cultural identities of those who belong to the modern youth-subcultural communities have been formed according to the topology and temporality of digital trends. To explain the worldview characteristics of the members of those subcultures the concept of "the New Middle Ages" was used to discover the values and pursuits of those who represent geek and chic subcultures. The study is based on the theoretical works of such classical authors as A. Toffler, and Z. Bauman, as well as current investigators of youth cultures. They are Calum Finister, Thomas V. Pollet, Nick Neave, Jessica McCain, Billy Wong. The chic subculture is oriented toward the imitation of visual images, consumer habits, and the way of life of successful (or seemed to be such) people. Glamorous followers need to receive approvals and likes from like-minded people. The geek subculture is more inner-sense-oriented. It unites intellectuals and activists who have common creative intentions. Originality. There have been analyzed the main attributes and features of such modern subcultures were conditionally named chic and geek. They were analyzed in the context of the concept of the New Middle Ages. Conclusions. The virtual user’s life world seems to be diverse only quantitatively, but qualitatively it is as narrow, mythopoetic, and esoterically uncritical as the world of the Medieval person, who used to live the whole life in the same place, mai in one’s village. But thanks to the merger of the IT industry with effective social management, the geek culture becomes a powerful super-subculture that defends values of social good, industrial productivity, and cultural creativity. Chic subculture creates new trends in fashion and art discourse. It develops modern lifestyles, its visual images with which our era will be associated in the future.